Pengolahan Limbah Laboratorium Kimia Secara Organik Menggunakan Kitosan dan Ekstrak Daun Abelmoschus dalam Kegiatan Praktikum - Rohana, Hana; Dzulummah, Zakiah; Yogasmana, Yopi (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Laboratory wastewater is hazardous to health and the environment; therefore, it must be treated correctly and precisely. Wastewater treatment involves coagulation and flocculation processes. Mostly, chemicals used as coagulants or flocculants are expensive and if used for a long time, they will damage the environment. In this study, wastewater treatment was carried out with environmentally friendly organic materials, namely using chitosan and Abelmoschus leaf extract. The aithis research was to examine the effectiveness of organic waste processing using chitosan and Abelmoschus leaf extract in relation to turbidity values. The research began with the optimization parameters (pH, coagulant/flocculant dosage, rate and stirring time) carried out using the Jar test. Optimum parameters were obtained from the lowest turbidity value for each parameter. From the research results, it was obtained that the optimum parameters were: pH 6.5; coagulant dose 400 mg/L; flocculant dose 105 mg/L; coagulant and flocculant stirring rate 50 rpm and 30 rpm; coagulant flocculant stirring time 12.5 minutes and 10 minutes.The optimum parameters applied to wastewater treatment. The results indicate that turbidity value in the wastewater before processing is an average of 359 NTU and the turbidity value after processing is an average of 13.31 NTU.To confirm the results of the study, statistical tests were carried out on the samples. It is resulting there was a significant level difference due to the addition of chitosan and Abelmoschus leaf extract.